Terminal uranium(V/VI) nitride activation of carbon dioxide and carbon disulfide: factors governing diverse and well-defined cleavage and redox reactions - Cleaves, Peter A.; Kefalidis, Christos E.; Gardner, Benedict M.; Tuna, Floriana; McInnes, Eric J.L.; Lewis, William; Maron, Laurent; Liddle, Stephen T. (Wiley-VCH Verlag, 2017)
The reactivity of terminal uranium(V/VI) nitrides with CE2 (E=O, S) is presented. Well-defined C=E cleavage followed by zero-, one-, and two-electron redox events is observed. The uranium(V) nitride [U(TrenTIPS)(N)][K(B15C5)2] (1, TrenTIPS=N(CH2CH2NSiiPr3)3; B15C5=benzo-15-crown-5) reacts with CO2 to give [U(TrenTIPS)(O)(NCO)][K(B15C5)2] (3), whereas the uranium(VI) nitride [U(TrenTIPS)(N)] (2) reacts with CO2 to give isolable [U(TrenTIPS)(O)(NCO)] (4); complex 4 rapidly decomposes to known [U(TrenTIPS)(O)] (5) with concomitant formation of N2 and CO proposed, with the latter trapped as a vanadocene adduct. In contrast, 1 reacts with CS2 to give [U(TrenTIPS)(κ2-CS3)][K(B15C5)2] (6), 2, and [K(B15C5)2][NCS] (7), whereas 2 reacts with CS2 to give [U(TrenTIPS)(NCS)] (8) and “S”, with the latter trapped as Ph3PS. Calculated reaction profiles reveal outer-sphere reactivity for uranium(V) but inner-sphere mechanisms for uranium(VI); despite the wide divergence of products the initial activation of CE2 follows mechanistically related pathways, providing insight into the factors of uranium oxidation state, chalcogen, and NCE groups that govern the subsequent divergent redox reactions that include common one-electron reactions and a less-common two-electron redox event. Caution, we suggest, is warranted when utilising CS2 as a reactivity surrogate for CO2.